Restoration of Boreal and Temperate Forests - Stanturf, John A. (CRC Press, 2005)
In recent years, restoration of forest ecosystems has gained much interest. Forestry research and management has undergone profound change over the last decade, and restoration has become a policy goal in many countries. Nevertheless, until now there has been no authoritative reference that consolidates the state of the art of forest restoration into one comprehensive volume. Written by internationally recognized authors, Restoration of Boreal and Temperate Forests summarizes the entire range of restoration protocols at both local and regional scales and documents and compares case studies of forest restoration projects in a geographically diverse range of temperate and boreal zones.